Colchicine과 oryzalin 처리에 의한 Cymbidium hybrids의 기내 배수화 효율 증진 - 황숙현(Sook-Hyun Hwang); 김미선(Mi-Seon Kim); 박소영(So-Young Park) (Weon'ye gwahag gi'sulji, 2015)
This study aimed to investigate the efficiency of colchicine and oryzalin in inducing polyploidy in two Cymbidium hybrids [Showgirl 'Silky' and Mystery Island 'Silk Road' (Silk Road-4)]. Colchicine was used at concentrations ranging from 50 to $500mg{·}L^{-1}$, with treatments lasting 1 to 3 weeks. Oryzalin was used at concentrations ranging from 3 to $20mg{·}L^{-1}$, with treatments lasting 3 to 6 days or 1 to 3 weeks. The survival rate of PLBs was better in colchicine than in oryzalin solutions. The ploidy levels were screened using flow cytometry. In C. Showgirl 'Silky', the highest chromosome doubling efficiencies were obtained with the 1-week treatment in $50mg{·}L^{-1}$ colchicine (60%) and the 2-week treatment in $5mg{·}L^{-1}$ oryzalin (46.7%). In C. Mystery Island 'Silk Road' (Silk Road-4), the highest chromosome doubling efficiencies were obtained with the 1-week treatment in $50mg{·}L^{-1}$ colchicine (16.7%) and the 3-day treatment in $10mg{·}L^{-1}$ oryzalin (6.7%). Colchicine was more efficient than oryzalin in terms of polyploidy induction. Furthermore, pre-treatment, which entailed poking 10 times with forceps, improved the efficiency of chromosome doubling. 본 연구는 우리나라 주요 난과식물 중 하나인 심비디움의 배수체 육종을 위한 기초자료를 얻고자 실시되었으며, 기내 심비디움의 PLBs에 colchicine과 oryzalin을 처리방법과 농도, 기간을 다양하게 하여 배수체 유도에 최적의 조건을 찾고자 수행하였다. Colchicine은 50, 100, 300, $500mg{·}L^{-1}$농도로 1, 2, 3주간 처리하였고 oryzalin은 3, 5, 10, $20mg{·}L^{-1}$농도로 1, 2, 3주 또는 3, 6, 9일간 처리하였는데 oryzalin에 비해 colchicine을 처리했을 때 생존율이 높게 나타났다. Flow cytometry를 이용하여 배수성을 검정해본 결과 Cymbidium Showgirl 'Silky'의 경우, colchicine은 $50mg{·}L^{-1}$농도로 1주간 처리 시 6배체 획득효율이 60%, oryzalin은 $5mg{·}L^{-1}$농도로 2주간 처리 시 6배체 획득효율이 46.7%로 가장 높게 나타났다. Cymbidium Mystery Island 'Silk Road'(Silk Road-4)의 경우, colchicine은 $50mg{·}L^{-1}$농도로 1주간 처리 시 6배체 획득효율이 16.7%, oryzalin은 $10mg{·}L^{-1}$농도로 3일간 처리시 6배체 획득효율이 6.7%로 가장 높게 나타났다. 즉, 두 hybrid 모두 oryzalin보다 colchicine을 처리했을 때 염색체 배가에 더 효율적이었다. 또한 처리 전 PLBs를 뾰족한 핀셋으로 10회 찌르는 방법을 통해 염색체 배가 효율을 향상시킬 수 있는 것으로 나타났다.